Influence of the training loading on the program paralympic junior sport school on the indexes of physical qualities of young tennis players 6-8 years - Loboda V.S; Mulik V.V; Dugina L.V; Harchenko T.P (Kharkov National Pedagogical University, 2012)
Influence of the training loading is considered on the program paralympic junior sport school on the indexes of physical qualities of young tennis players 6-8 years. The aim of experiment was an exposure of dynamics of development of motive internalss of young tennis players during three years (6-8 years) under the influence of the training loading on the program of children sport school. In experiment took part the group of initial preparation in an amount 25 children (boys). Research was conducted within the framework of the operative (employments), current (mezocycle) and stage (annual) planning of training process.